Enhancing Infant Immunization Rates: Determinants of Complete Routine Vaccination in an Urban Indonesian Primary Health Center - Lutfi Agus Salim; Muthmainnah Muthmainnah; Alif Fatimatuz Zahro; Damai Arum Pratiwi; Ira Nurmala; Chung-Ying Lin; Dini Yulia Restuti; Annisa Clara Salsabila (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Infant immunization is crucial in reducing mortality and morbidity, aligning with the Sustainable Development Goals (SDGs) to promote health and well-being. In Indonesia, routine immunization for infants aged 0-12 months includes essential vaccines and newer antigens like PCV and Rotavirus. Maternal beliefs significantly influence immunization completion. This study examines factors affecting mothers' decisions regarding complete immunization in the Banyu Urip Health Center area using the Health Belief Model. Methods: A cross-sectional study was conducted on 86 mothers with infants aged 12-24 months to assess immunization completeness during their first year. The study analyzed the relationship between maternal perceptions, such as susceptibility, severity, benefits, barriers, self-efficacy, and cues to action and immunization behavior. Results: Findings showed a moderate relationship between perceived susceptibility, severity, barriers, and cues to action with immunization behavior. A strong correlation was observed between perceived benefits, self-efficacy, and participation in complete immunization. Mothers with higher risk perception, awareness of severity, strong belief in benefits, and self-efficacy, along with strong cues to action and fewer barriers, were more likely to ensure full immunization for their infants. Conclusion: The study highlights the importance of strengthening awareness and reducing barriers to improve immunization rates. Enhancing maternal self-efficacy and addressing perceived obstacles can increase full immunization coverage, ensuring better health outcomes for infants.